Intraoperative Hypoxia Independently Associated With the Development of Acute Kidney Injury Following Bilateral Orthotopic Lung Transplantation. Issue 4 (6th May 2021) - Knight, Joshua; Hill, Adam; Melnyk, Vladyslav; Doney, Luke; D'Cunha, Jonathan; Kenkre, Tanya; Subramaniam, Kathirvel; Howard-Quijano, Kimberly
Abstract : Background: Acute kidney injury (AKI) is a common postoperative complication in bilateral orthotopic lung transplant (BOLTx) recipients, but the contribution of intraoperative variables is not well defined. The authors hypothesized that intraoperative hypotension as well as hypoxia and vasopressor use would be associated with the development of postoperative AKI after BOLTx in patients without pre-existing renal dysfunction. Methods: The authors performed a retrospective analysis of patients undergoing BOLTx at a single center between 2013 and 2017. Intraoperative variables of hemodynamics included duration of mean arterial pressure <55, <60, and <65 mm Hg; duration of oxygen saturation <90%; and vasoactive-inotropic score (VIS). Associations between the occurrence of AKI and intraoperative hypotension, hypoxemia, and VIS were evaluated while controlling for significant confounding variables. Results: AKI occurred in 177 (72%) of 245 patients in postoperative days 1–7. Notable significant differences in univariate analyses included cumulative mechanical support time, maximum VIS, peripheral oxygen saturation <90% for >15 min, total minutes oxygen saturation <90%, and surgery duration in minutes. There was no significant difference in intraoperative hypotension measured as a duration >15 min for mean arterial pressure <55, <60, or <65 mm Hg. Multivariate logistic regression revealed preoperative creatinine (Odds ratio [OR], 7.77; confidence interval [CI], 1.96-30.83; P = 0.004), surgery duration (OR, 1.004; CI, 1.002-1.007; P = 0.002), and oxygen saturation (OR, 2.06; CI, 1.01-4.24; P = 0.049) <90% for >15 min to be independently associated with AKI. Conclusions: This study revealed that >15 min of intraoperative hypoxia was independently associated with postoperative AKI after BOLTx. Abstract :